A Survey of the Protective Effect of Vitamin B6 on Linezolid-Associated Hematological Dyscrasia: Vitamin B6 and linezolid hematological toxicities - Talaie, Haleh; Nazari, Maryam; Salavati-esfahani, Mehdi; Hosseini, Sayed Masoud; Barari, Behjat (Iranian Journal of Pharmaceutical Sciences, 2021)
Hematological toxicities are considerable side effects of linezolid, which can restrict its administration. This study aims to evaluate the protective effect of vitamin B6 on linezolid-induced hematological dyscrasia, i.e., thrombocytopenia and anemia in poisoned patients. In this quasi-experimental (non-randomized, non-blinded) study, a number of 28 patients treated with linezolid and vitamin B6 were matched with 50 patients who received only linezolid. The hematological factors, including red blood cells (RBCs), hemoglobin (Hb), hematocrit (Hct), and platelets (PLTs) were assessed at baseline and on days 0, 1, 3, 5, and 7 during the linezolid treatment coarse. There were no considerable differences between the two groups in demographic characteristics, poisoning, vital signs, baseline laboratory test results, and mortality rates. Overall, patients who received linezolid+B6 had significantly higher RBCs, Hb, and Hct than those treated with linezolid alone (P < 0.05). Unexpectedly, patients in the treatment group had lower PLT counts compared to the control group with no significant differences (P > 0.05). According to our findings, the co-administration of vitamin B6 and linezolid was accompanied by a lower risk of anemia but no impact on preventing or reducing thrombocytopenia in patients with gram-positive bacterial infections.